Early Onset Multiple Primary Tumors in Atypical Presentation of Cowden Syndrome Identified by Whole-Exome-Sequencing - Cavaillé, Mathias; Ponelle-Chachuat, Flora; Uhrhammer, Nancy; Viala, Sandrine; Gay-Bellile, Mathilde; Privat, Maud; Bidet, Yannick; Bignon, Yves-Jean (Frontiers in Genetics, 2018)
A family with an aggregation of rare early onset multiple primary tumours has been managed in our oncogenetic department : proband developed between 31 and 33 years old 4 early onset carcinomas including successively acral melanoma, bilateral clear cell renal carcinoma and follicular variant of papillary thyroid carcinoma. Proband’s mother developed orbital lymphoma and small intestine MALT lymphoma respectively at 41 and 50 years old. Whole-exome sequencing (WES) of the nuclear family (proband, parents and brother) was performed and identified de novo deleterious heterozygous mutation c.1003C>T (p.Arg335X) in phosphatase and tensin homolog (PTEN) gene in proband. Furthermore, WES allowed the analysis of the nuclear family’s genetic background in this study, and identified two candidate modifier genes: CEACAM1, and MIB2. CEACAM1, a tumor suppressor gene, presents loss of expression in clear cell renal carcinoma and is involved in proliferation of B cells. It could explain in part the phenotype of proband's mother and occurrence of clear cell renal carcinoma in proband. Deleterious mutation in MIB2 gene is associated with melanoma invasion, and could explain the occurrence of melanoma in proband. Cowden syndrome, a hereditary autosomal dominant disorder, is associated with increased risk of muco-cutaneous features, hamartomatous tumors and cancer. This atypical presentation, including absence of muco-cutaneous lesions, 4 primary early onset tumours and bilateral clear cell renal carcinoma, has never been described before. Those encourage proposing starting screening of renal carcinoma and melanoma respectively at 30 and 10 years old. This also encourages including PTEN gene in panel genes testing in the context of early onset renal carcinoma, whatever the histological subtype. Further studies are required to determine implication of CEACAM1 and MIB2 in the severity of Cowden syndrome in proband and occurrence of early onset MALT lymphoma in his mother.